Shaping the Surface Deformation of Central and South Tibetan Plateau: Insights From Magnetotelluric Array Data. Issue 9 (27th August 2020) - Dong, Hao; Wei, Wenbo; Jin, Sheng; Ye, Gaofeng; Jones, Alan G.; Zhang, Letian; Jing, Jian'en; Xie, Chengliang; Yin, Yaotian
Abstract: The ongoing India‐Asia collision since the Paleogene created the Tibetan Plateau, the most prominent elevated plateau on our planet. This convergence also contributed to the formation of two distinct types of active surface deformation of the plateau, namely, north–south trending normal fault systems and "conjugate" strike‐slip fault systems. The tectonics and geodynamic mechanism(s) behind this curious combination are still unclear, despite numerous theories proposed over past decades. Here we present a new three‐dimensional, lithospheric‐scale, electrical conductivity model with unprecedented resolution of the central part of Tibetan Plateau derived from the SINOPROBE magnetotelluric array data set and discuss its inferences related to this question. Our model reveals contrasting conductivity structures corresponding to the surface deformation patterns, namely, highly conductive lower crustal anomalies beneath the graben systems in the Lhasa and Qiangtang terranes and moderately resistive crustal features in the strike‐slip region near Bangong‐Nujiang Suture Zone. With the help of experimentally calibrated constraints between conductivity and melt fraction, the conductivity model and the inferred lateral viscosity distribution together suggest a weak lower crust beneath the graben regions, compared to a stronger crustal rheology associated with the strike‐slip zone. Here we expand the previously proposed "extensional extrusion" tectonic model in central Tibet to interpret our conductivity model and other geophysical/geodesic observations. The weak rheology under a N‐S directed primary stress may have caused the east–west extension of the graben regions, which further aides the eastward extrusion of the conjugate strike‐slip zone and eventually shapes the surface deformation of central Tibetan Plateau into its current, complex pattern. Plain Language Summary: The collision between the Indian and Asian continents built the Tibetan Plateau, the highest plateau in the world. This active collision also formed distinctly different types of large‐scale geological structures on the plateau surface. Among the most important features on the plateau, the origin of the N‐S directed normal (or spreading) fault zones in two regions named Lhasa and Qiangtang, and the NW/SE directed slip fault zones between these two regions are still unclear. In order to understand the generation of those structures, we use a geophysical imaging method called magnetotellurics to measure the naturally occurring electromagnetic waves in the earth. We model and analyze these magnetotellurics data to obtain the deep structure beneath those surface structures, using sophisticated computer codes. We find that the two dominant but different types of those structures are most likely due to the different strengths of the deep crust. This strength difference can lead to a mechanical stress contrast, which further builds the distinctly different surface structures. These kinds of deep physical structure differences have not been detected for the area before. Our study provides information on the strength of the crust, which is critical to understand the deep mechanic process of the earth. Key Points: Magnetotelluric data collected in central and south Tibetan Plateau highlight distinct variations in the crustal conductivity structure Empirical relationship between conductivity and viscosity helps identifying stark rheological contrast in the lower crust Rheological contrast can lead to divergent mechanical deformations, which further shape the complex surface structure of the Plateau